Motivations for the treatment of crack users in a therapeutic community - Maycon Rogério Seleghim; William Campo Meschial; Beatriz Ferreira Martins; Cinthia Lopes Barboza; Sueli Aparecida Frari Galera; Magda Lúcia Félix de Oliveira (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: Knowing the motivation of crack users for treatment in hospital environments. Method: Descriptive and qualitative search, using the design of some cases. Twenty male crack users, aged over 18 years old, hospitalized in a Therapeutic Community in Southern Brazil, were interviewed. A semi-structured interview was used and the data were analyzed by their thematic content. Results: Were found three categories that reflect the treatment motivations: perception of the crack harmful consequences; the compulsive use of drugs as the treatment initiation; and, the family participation looking for a treatment. Conclusion: Significant events (turning points) favored the interruption of the crack use and the family assumed a very important place to the users behavior in relation to the use of the drug, exclusively. Descriptors: Street drugs, Crack Cocaine, Substance Abuse Treatment Centers, Family.